(untitled) (Research, Society and Development, 2022)
The world population is aging rapidly due to declining fertility rates and increasing life expectancy. In this way, the Nurse can assist in healthy aging through actions in the family health strategy to promote autonomy, independence and encourage self-care for the elderly. Based on this, this study aimed to analyze the difficulties encountered by nurses in promoting healthy aging in the family health strategy. It was a descriptive field study of qualitative nature, carried out with 10 nurses from the Family Health Strategy (ESF) in the city of Piripiri-PI. Data collection was carried out through semi-structured interviews with open questions. Data analysis was performed according to the content analysis proposed by Bardin. How many results, showed through these studies that the process of healthy aging requires a special look, and a better quality of life should be offered to the elderly, through family participation and professional monitoring, ensuring and promoting physical, psychological and social well-being. The present study made it possible to highlight the difficulties encountered by nurses in promoting healthy aging and suggests that Primary Health Care nurses reflect on the findings of this research. Finally, other related works become necessary for a better understanding of the subject studied here.